ChemInform Abstract: Pd/C‐Mediated Synthesis of (Z)‐3‐Alkylidenephthalides of Potential Pharmacological Interest. Issue 37 (22nd August 2013) - Rambabu, D.; Kumar, G. Pavan; Kumar, Barange Deepak; Kapavarapu, Ravikumar; Rao, M. V. Basaveswara; Pal, Manojit
Abstract The coupling—cyclization of o‐bromobenzoic acid with terminal alkynes uses a bimetallic Pd‐C/Cu catalyst system.